Correlation between oral health knowledge and awareness and periodontal status in non-syndromic cleft lip and palate patients undergoing orthodontic treatment: a cross-sectional study - Rezaumami, Debrinna; Evangelina, Ida Ayu; Laviana, Avi; Sayuti, Elih; Saadun Tarek, Sharifah Wade'ah Wafa Syed (Padjadjaran Journal of Dentistry, 2024)
Introduction: Children and adolescents with non-syndromic cleft lip and palate (CLP) experience a higher prevalence of caries and periodontal disease compared to those without CLP. This increased prevalence is often attributed to greater plaque accumulation, which can lead to gingival inflammation and periodontal disease. This study aims to analyze the correlation between oral health knowledge and awareness and the periodontal health status of orthodontic patients with cleft lip and palate (CLP).Method: This study used a cross-sectional approach. The study population consisted of orthodontic patients with non-syndromic CLP who met the inclusion criteria. The research was conducted at the UNPAD Dental Teaching Hospital (RSGM Unpad) from March to May 2024. Twenty-seven participants with non-syndromic CLP were included in the study. A non-probability, purposive sampling technique was employed. oral health knowledge and awareness were assessed using questionnaires, while periodontal health examinations were evaluated using the Community Periodontal Index (CPI). Correlation analyses were performed using Kendall's Concordance Correlation (W). Additionally, Spearman Rank Correlation Analysis was conducted to identify the dominant variables. Results: The analysis revealed a Kendall's Concordance Correlation (W) of 0.544, which is statistically significant (p < 0.0001), indicating a 54.4% relationship between the variables. The correlation between knowledge and periodontal health status in orthodontic patients with non-syndromic CLP was 11.16%, with a p-value of 0.0443 (p < 0.05) and an r-value of 0.33. The correlation between awareness of oral health and periodontal health status in these patients was 19.85%, with a p-value of 0.0099 (p<0.05) and an r-value of 0.45. Conclusion: There is a weak correlation between knowledge and awareness of oral health and the periodontal health status in non-syndromic CLP patients undergoing fixed orthodontic treatment.